Development of very high frequency plasma enhanced chemical vapour deposition for nanostructure silicon carbide thin film deposition - Omar, Muhammad Firdaus (2016)
Silicon carbide (SiC) is a semiconductor material which has received a great deal of attention due to its outstanding mechanical properties, chemical inertness, thermal stability, superior oxidation resistance, high hardness, wide band gap and relatively low weight for applications in high frequency and high power systems in extreme environment. SiC particularly amorphous SiC (a-SiC) and polycrystal SiC (pc-SiC) have important roles for several applications such as microelectromechanical systems (MEMS) or nanoelectromechanical Systems (NEMS), thermoelectric cooling (TEC), optoelectronic devices, solar cell or as a substrate for deposition of graphene. However, the present a-SiC and pc-SiC thin film materials are less competitive materials for these applications. Previous researchers reported that, scaling down bulk SiC to nanostructure (ns-SiC) has shown performance improvement in those applications. The structure of ns-SiC thin film can be either in single crystal, polycrystal or nanocrystal (embedded in amorphous layers) forms with layer thickness or grain size in nanometer range. The conventional plasma enhanced chemical vapour deposition (PECVD) technique is mainly needed to grow a-SiC or pc-SiC thin film. High deposition temperature is required in order to improve its crystallinity. However, high deposition temperature would induce thermal stress in deposited thin film. Thus, very high frequency-PECVD (VHF-PECVD) with 150 MHz RF was designed and developed in this work based on direct plasma mode with capacitive couple discharge (CCD) configuration with the aim to deposit ns-SiC at relatively low deposition temperature compared to conventional PECVD. The plasma profile of argon (Ar), hydrogen (H2), silane (SiH4) and methane (CH4) of the system were characterized using optical emission spectrometer (OES). This system is found to be able to fully dissociate SiH4 plasma at room temperature. Meanwhile Ar and H2 mixture with CH4 plasma is needed for CH4 to fully dissociate at room temperature. The effects of three major parameters, namely the type of dilution gas, CH4 flow rate and RF power on the properties of the deposited thin film were investigated. The formation of ns-SiC crystal structure is observed at relatively low growth temperature of about 400 °C. Nanocrystal formation is enhanced when H2 and Ar are added to plasma mixture and the smallest diameter obtained is about 1.5 nm. The trend shows that, the growth mechanism changes from layer-island mechanism to layer-layer mechanism and root mean square roughness (Rrms) improves from 84.43 nm to 0.74 nm when CH4 flow rate is increased. Single crystal epilayer is successfully deposited with a crystal structure assigned as 4H-SiC and confirmed of having 3.26 eV optical band gap. Increasing CH4 flow rate results in the luminescence emission of ns-SiC to be shifted from green (~ 518 nm) dominant emission to UV-B (~294 nm) dominant luminescence emission. This indicates that the deposited ns-SiC has potential for optoelectronic application in visible light to medium UV range.